6x+6+x=3+2x-17

Simple and best practice solution for 6x+6+x=3+2x-17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+6+x=3+2x-17 equation:


Simplifying
6x + 6 + x = 3 + 2x + -17

Reorder the terms:
6 + 6x + x = 3 + 2x + -17

Combine like terms: 6x + x = 7x
6 + 7x = 3 + 2x + -17

Reorder the terms:
6 + 7x = 3 + -17 + 2x

Combine like terms: 3 + -17 = -14
6 + 7x = -14 + 2x

Solving
6 + 7x = -14 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
6 + 7x + -2x = -14 + 2x + -2x

Combine like terms: 7x + -2x = 5x
6 + 5x = -14 + 2x + -2x

Combine like terms: 2x + -2x = 0
6 + 5x = -14 + 0
6 + 5x = -14

Add '-6' to each side of the equation.
6 + -6 + 5x = -14 + -6

Combine like terms: 6 + -6 = 0
0 + 5x = -14 + -6
5x = -14 + -6

Combine like terms: -14 + -6 = -20
5x = -20

Divide each side by '5'.
x = -4

Simplifying
x = -4

See similar equations:

| 7+4x-3=9x+10-6x | | x+x+x+1=x+17 | | y=0.42x+19.26 | | 0.34x-2.71=1.28 | | 5a-3b=6c | | 6x-7=2x+12 | | 5z+17z=176 | | Z=-24 | | 3x+4y-2+x+5y+3=0 | | 6x+6+x=3+2x-7 | | 3m+27=57 | | m/9+10=16 | | 5x*3f= | | 11k+6=39 | | 0.3x-2.8=4.9 | | w^2-7wf-18f^2= | | 12k+3=63 | | N=.05x-98.75 | | 6w-5=25 | | 8a-10=22 | | 2x+5=2(4+x) | | y=-10x | | -5x-18=7 | | 1.25x-3.34=7 | | 2x+4(x-8)=3(2x+12) | | (2m+9)(m-7)=0 | | =x^2+40x-100 | | -2x-6-3x=1 | | 0.67x-3.5=2.25 | | =2x^2+8x+8 | | x=2+0.5y | | =2x^2 |

Equations solver categories